Trading places: Inclusive cities and market vending in the Pacific Islands. (9th October 2019) - Keen, Meg; Ride, Anouk
Abstract : Rapid population growth in Pacific island cities far exceeds employment opportunities and is contributing to rising urban inequality and social exclusions. Livelihoods in the informal urban sector, such as market vending, provide much needed income, rural–urban connectivity and food security, but remain largely excluded from policy and planning frameworks. Spatial, economic and social exclusions limit vendors' economic advancement, their influence over decision‐making, and their access to basic services. Local communities close to informal markets fill some of the gaps left by the policy neglect, but investment and strategic management remains inadequate when vendors do not have secure market places and recognised rights to work. This article reports on a study of three informal markets in Honiara, Solomon Islands. These markets lack legal status but make significant contributions to urban development and economic opportunities. Drawing on surveys and focus groups with vendors and urban decision‐makers we explore the impact of informal markets on urban economies, how social and institutional relationships hinder vendors' economic advancement, and the opportunities to create more inclusive livelihoods that could contribute to equitable cities.